2014
DOI: 10.1108/ijphm-04-2014-0020
|View full text |Cite
|
Sign up to set email alerts
|

The False Claims Act: a review and policy recommendations

Abstract: Purpose – The purpose of the study is to review The False Claims Act (FCA) settlements and challenges facing the industry to suggest the motivation behind firms’ alleged fraudulent activity. FCA has been applied against pharmaceutical companies by the US Government to combat marketing fraud including kickbacks, improper pricing and off-label promotion. The interests of the US Government and medical professionals are also considered. Changes to the law governing pharmaceutical marketing practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Ethical issues and unethical behaviour associated with pharmaceutical companies (2008-2017) Sillup and Porth (2008) analysed the USA leading newspaper articles and found that drug pricing, data disclosure, importation and drug safety were some of the ethical issues identified in 2004 and 2005. Further, improper pricing specifically drug pricing, orphan drug pricing, bribery risk, medical research on the contract were ethical issues (Adobor, 2012;Schramm et al, 2014;Hemphill, 2010). Williams- Jones and Ozdemir (2008) argue that truth in advertising and protecting intellectual property were ethically challenging issues for pharmaceutical companies.…”
Section: Pharmaceutical Companiesmentioning
confidence: 99%
“…Ethical issues and unethical behaviour associated with pharmaceutical companies (2008-2017) Sillup and Porth (2008) analysed the USA leading newspaper articles and found that drug pricing, data disclosure, importation and drug safety were some of the ethical issues identified in 2004 and 2005. Further, improper pricing specifically drug pricing, orphan drug pricing, bribery risk, medical research on the contract were ethical issues (Adobor, 2012;Schramm et al, 2014;Hemphill, 2010). Williams- Jones and Ozdemir (2008) argue that truth in advertising and protecting intellectual property were ethically challenging issues for pharmaceutical companies.…”
Section: Pharmaceutical Companiesmentioning
confidence: 99%